Simulation of complex environment - Low, Charis Enhui. (2012)
Radio propagation in wireless communications are affected by propagation mechanisms, namely reflection, diffraction and scattering. These cause the signal to experience fading, and result in multipath effect received at the receiver antenna. Radio propagation provides a means to effectively trace the signal that propagates from the transmitter to the antenna. This report describes experiments that were conducted during the course of the FYP. Ray tracing simulations modeled after the actual test set-up have been run in a simulator, Wireless InSite, and the results have been presented. Comparison of the received signals obtained from the actual environment and that of the simulation have been done, and the results prove that ray tracing is a suitable means of analyzing the signal.